Mezektodermalny mięśniak gładkokomórkowy – opis przypadku - Sojka, Paulina; Pogrzebielski, Arkadiusz; Orłowska-Heitzman, Jolanta; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Purpose: The aim of this report is to present a case of mesectodermal leiomyoma of the ciliary body. Material and methods: In the left eye of the 15 years old female patient presenting 2 months history of deterioration of visual acuity a medium-pigmented, dome-shaped tumor at the inferotemporal side was detected. It measured 21.6 mm in base diameter 11.2 mm in thickness and was revealed with imaging techniques such as ultrasound, MRI and orbital radiography. Taking into consideration all clinical features, despite patients’ young age, malignant melanoma of the ciliary body was suspected. Due to the size of the tumor and the impossibility of conducting conservative treatment the globe was eventually enucleated. Results: The final diagnosis was established on the basis of histopathological microscopic examination and immunohistochemical stains. The co-expression of muscular (SMA, caldesmon, desmin), as well as neural markers (S-100 protein and synaptophysin), has been proved. Conclusions: Mesectodermal leiomyoma of the ciliary body is an extremely rare benign tumor, which originates from neural crests. It exhibits features of both muscular and neural differentiation.